2020
DOI: 10.3390/ma13092012
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Resistance of Zirconia-Reinforced Lithium Silicate Ceramic Crowns Cemented with Conventional or Adhesive Systems: An In Vitro Study

Abstract: In recent years, Zirconia-reinforced Lithium Silicate ceramic (ZLS), combining lithium-silicate and zirconia features, has shown to have excellent mechanical and aesthetic characteristics. Thus, the aim of this study was to compare the fracture strength of ZLS single crowns cemented with two different cementation techniques. Twenty crowns were realised and cemented on teeth replicas achieved from an extracted premolar human tooth. The samples were divided into two groups of 10 specimens each, Glass-ionomeric c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 47 publications
(66 reference statements)
0
18
2
Order By: Relevance
“…However, from a clinical standpoint, the findings need to be interpreted with caution, as the fracture loads do not completely represent failures in intra-oral use. The fracture resistance values (4677 ± 1742 N) found in this report for ZLS crowns were higher than the mean values of 3056 N to 3712 N reported in other recent papers [ 49 , 58 , 75 ] on ZLS crowns. However, the results of this study also matched the findings of some papers that found fracture strength values of 4570 ± 1242 N [ 76 ] and 4100 N [ 58 ], albeit with milled monolithic LDS crowns.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…However, from a clinical standpoint, the findings need to be interpreted with caution, as the fracture loads do not completely represent failures in intra-oral use. The fracture resistance values (4677 ± 1742 N) found in this report for ZLS crowns were higher than the mean values of 3056 N to 3712 N reported in other recent papers [ 49 , 58 , 75 ] on ZLS crowns. However, the results of this study also matched the findings of some papers that found fracture strength values of 4570 ± 1242 N [ 76 ] and 4100 N [ 58 ], albeit with milled monolithic LDS crowns.…”
Section: Discussioncontrasting
confidence: 83%
“…A self-adhesive resin cement was used in the current paper for cementation of crowns on the master dies. Notable differences in fracture loads of ZLS crowns have been reported by previous studies [ 29 , 49 ] when used with different types of cements, and the results might have also been different in this study, too, if other luting cements (glass ionomer or resin-modified glass ionomer) were used instead of or in comparison to self-adhesive resin. A single CAD/CAM system and 5-axis milling machine were used in this study for fabricating both types of crowns, thus providing standardization and eliminating the influence of software and milling unit differences on the final outcomes.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…In materials science, contemporary CAD/CAM blocks are categorized into three groups, namely metal-based (e.g., titanium alloy [ 4 ] and Co-Cr alloy [ 5 ]), ceramic-based (e.g., feldspathic porcelain [ 6 ], lithium disilicate glass [ 7 ] and zirconia [ 8 ]), or resin-based (e.g., acrylic resin [ 9 ] and resin composite (hereafter composite) [ 10 ]). An investigation of new composites already in use (e.g., poly(ether-ether-ketone) (PEEK) [ 11 ]) and some interesting research on new materials with hierarchized geometry [ 12 ] and biomechanical problems [ 13 , 14 , 15 ] (i.e., bruxism) have also been conducted thus far.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of defects at the tooth/restoration interface, represents an early sign of adhesive failure before the longevity of the restoration itself is compromised [ 12 ]. Over the years, different adhesion protocols, alternative materials, and substrate pretreatment procedures able to influence the degree of adhesion have been studied [ 13 , 14 , 15 , 16 ]. In this regard, chemical or mechanical dentin pretreatments are procedures that increase the roughness of the treated surface and may influence the adhesion strength of a bonding agent by increasing the contact area between the dentine and the adhesive surface [ 17 ].…”
Section: Introductionmentioning
confidence: 99%